Financial performance investigation of PT Acset Indonusa Tbk based on Du Pont and Common Size analysis - Reswita, Jihan; Siregar, saparuddin; Kamila, K (Dinasti Publisher, 2024)
The Du Pont Analysis is a method of evaluating financial performance that breaks down Return on Equity into its main components. Common Size Analysis involves presenting financial statements by converting each account into a percentage of total revenue or assets. This research aims to investigate the financial performance of PT. Acset Indonusa Tbk, a construction company listed on the Indonesia Stock Exchange (IDX), during the period 2018-2022. The approach used is qualitative with a quantitative approach using the Du Pont System and Common Size methods. Data collection was conducted through literature review and documentation study. Secondary data were obtained from the company's financial statements downloaded from the official website. The results of this study indicate that the financial performance of PT. Acset Indonusa Tbk for the period 2018-2022 is considered poor. This is due to, of the five variables analyzed in the Du Pont System method, namely Net Profit Margin (NPM), Total Assets Turnover (TATO), Return on Assets (ROA), Equity Multiplier (EM), and Return on Equity (ROE) are below industry standards and only EM has increased. In the Common Size Analysis, it is shown that PT Acset Indonusa Tbk has faced several challenges in recent years, such as declining profitability, increasing expenses, and fluctuating funding structures.